THE ISLAMIC LAW REVIEW ON MANAGEMENT OF THE SOCIAL SECURITY ORGANIZING AGENCY (BPJS) - Pandi Rais; Shahrul bin Abd Shofi; Erina Sonia; Sulis Setyoningsih (Qawanin: Jurnal of Economic Syaria Law, 2020)
The Social Security Organizing Agency (BPJS) is a legal entity formed in the aspect of a health insurance program. BPJS is part of the JKN (National Health Insurance) which has the aim of ensuring the health of the entire citizen . To measure whether the BPJS for heath has been able to realize its goals, it is necessary to discuss this matter through this journal. With the journal method, the descriptive type method, and the data collection technique used is library research. Then the data is analyzed by descriptive analysis method and associated with the facts. Data shows that the BPJS is a mutual assistance guarantee program, participation is mandatory for all Â citizens and is not selective, as well as the existence of a contribution system. Facilities provided include First Level Health Facilities (FKTP), Advanced Level Referral Health Facilities (FKRTL), supporting health facilities, all of which are provided to address health problems since the level of minor illness. However, in the development of the implementation of the BPJS program, several problems emerged, which eventually affected the level of public health. The results of the Bahtsul Masail of PBNU in the Bahtsul Masail commission session at the Bahrul Ulum Nahdatul Ulama Islamic Boarding School, decided that the Social Security Organizing Agency (BPJS) was halal and could be used for all groups in the framework of health insurance in Indonesia. The Social Security Organizing Agency (BPJS) is a legal entity formed in the aspect of a health insurance program. BPJS is part of the JKN (National Health Insurance) which has the aim of ensuring the health of the entire citizen . To measure whether the BPJS for heath has been able to realize its goals, it is necessary to discuss this matter through this journal. With the journal method, the descriptive type method, and the data collection technique used is library research. Then the data is analyzed by descriptive analysis method and associated with the facts. Data shows that the BPJS is a mutual assistance guarantee program, participation is mandatory for all citizens and is not selective, as well as the existence of a contribution system. Facilities provided include FirstLevel Health Facilities (FKTP), Advanced Level Referral Health Facilities (FKRTL), supporting health facilities, all of which are provided to address health problems since the level of minor illness. However, in the development of the implementation of the BPJS program, several problems emerged, which eventually affected the level of public health. The results of the Bahtsul Masail of PBNU in the Bahtsul Masail commission session at the Bahrul Ulum Nahdatul Ulama Islamic Boarding School, decided that the Social Security Organizing Agency (BPJS) was halal and could be used for all groups in the framework of health insurance in Indonesia.